Beyond Conquest: Decolonizing Adventure Sports through Outdoor Counterstories - Denisa Krásná (Acta Universitatis Carolinae Studia Territorialia)
This paper explores decolonial outdoor counterstories written by minoritized adventure athletes, focusing particularly on Indigenous voices within the sports of rock climbing, (ski) mountaineering, highlining, and, marginally, white-water kayaking. Traditional adventure narratives have long been dominated by white, masculine figures who glorify conquest, reinforcing patriarchal, colonial, and anthropocentric ideas that marginalize diverse perspectives and contribute to environmental degradation. In contrast, contemporary decolonial counterstories challenge these exclusionary notions, reclaiming outdoor spaces and redefining success not as domination, but as a deep connection with nature, community, and personal well-being. By presenting Indigenous and other marginalized perspectives, these narratives critique and subvert Western colonial ideologies, promoting a more inclusive and ecologically mindful approach to outdoor sports. This paper argues that these counterstories contribute to the creation of a collective decolonial outdoor counternarrative that could inspire pro-environmental actions among adventure athletes who experience climate anxiety. The analysis highlights how these athletes are not only reshaping the cultural landscape of outdoor sports but also advocating for a shift from competitive dominance to collaborative coexistence, thereby supporting a more equitable and sustainable interaction with the natural world.